2014
DOI: 10.1159/000369570
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and Breast Cancer Risk

Abstract: Reproduction is doubtlessly one of the main biological meanings of life. It is therefore not surprising that various aspects of reproduction impact on breast cancer risk. Various developmental levels may become targets of breast tumorigenesis. This review follows the chronologic sequence of events in the life of a female at risk, starting with the intrauterine development. Furthermore, the influence of both contraceptive measures and fertility treatment on breast cancer development is dealt with, as well as va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Breast feeding has consistently been associated with lower risk of breast cancer in epidemiological studies. 39 Other reproductive factors such as older age at menarche might also associate with risk, possibly depending on the breast cancer subtype 40 A weakness in our study was that we were unable to adjust for reproductive factors other than parity and number of births; if such factors were associated with change in alcohol intake, results could be biased due to residual confounding.…”
Section: Discussionmentioning
confidence: 97%
“…Breast feeding has consistently been associated with lower risk of breast cancer in epidemiological studies. 39 Other reproductive factors such as older age at menarche might also associate with risk, possibly depending on the breast cancer subtype 40 A weakness in our study was that we were unable to adjust for reproductive factors other than parity and number of births; if such factors were associated with change in alcohol intake, results could be biased due to residual confounding.…”
Section: Discussionmentioning
confidence: 97%
“…Other risk factors are related to hormones, including early age of menarche, late onset of menopause, nulliparity, late age of first parity, lactation, use of oral contraceptive and hormone replacement therapy (6,7). Moreover, various life style-related factors, such as alcohol consumption and obesity, and disease conditions (e.g., diabetes), also contribute to the occurrence of breast cancer (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that prolonged lactation protects against the development of BC is one of the oldest and the most enduring hypotheses concerning the etiology of this neoplasm. Age at menarche and BC risk are probably indirectly associated, research estimate that the risk of BC can be reduced 10-20% for each year menarche is delayed, the results of a large study revealed that for each two-year delay in one set of menstruation, BC risk was reduced by about 10% (36) . In this study, most of the cases (55.9%) were started menstruation between the age of 13-14 years old and only 17.6% started menarche at earlier age.…”
Section: Discussionmentioning
confidence: 99%